RELIGIOUSTY AND ISLAMIC NORMATIVISM IN PORNOGRAPHY AS A SOCIAL PHENOMENON - Muhammadong Muhammadong (Aqlam: Journal of Islam and Plurality, 2023)
Abstrac: This article is to find out in the study of Islamic normativism about pornography as a social phenomenon caused by technological advances and the development of social media in people's lives. In the Islamic view, pornography is certainly strictly prohibited because it has an impact on moral decadence for the perpetrator. In Islamic studies, there is no clear mention of pornography because what is explained is only the issue of aurat and the consequences of adultery behavior that can damage the cultivation of life if not anticipated. Analysis of pornography in the current context must get answers from religious teachings so that the problems faced can be solved humanely so that the interpretation developed is not based on assumptions but through Islamic normative studies. Keywords: Reinterpretation, Islamic, Pornography, Social Media, TechnologicalAbstrak: Artikel ini untuk mengetahui dalam kajian normativisme Islam soal pornografi sebagai sebuah fenomena sosial yang diakibatkan salah satunya karena kemajuan teknologi dan perkembangan media sosial dalam kehidupan masyarakat. Dalam pandangan Islam, pornografi tentu sangat dilarang karena berdampak pada dekadensi moral bagi pelakunya. Dalam kajian keislaman tidak disebutkan secara jelas tentang pornografi  karena yang dijelaskan hanya persoalan aurat dan akibat yang ditimbulkan dari perilaku perzinahan yang dapat merusak tatanam kehidupan apabila tidak diantisipasi. Analisis tentang pornografi dalam konteks kekinian harus mendapat jawaban dari ajaran keagamaan agar persoalan yang dihadapi dapat diselesaikan secara manusiawi sehingga interpretasi yang dikembangkan bukan atas dasar asumsi akan tetapi melalui kajian normatif keislaman. Kata Kunci: Reinterpretasi, Islam,  Pornografi, Media Sosial, Tekhnologi